Aminothiaindanone as an Accessible Scaffold for a Three-Point Chemical Diversity - Zipfel, Pauline; Lalut, Julien; Sopková-de Oliveira Santos, Jana; Rochais, Christophe; Dallemagne, Patrick (Synthesis, 2021)
Aminothiaindanone heterocycle appears to be a scaffold of interest in medicinal chemistry. To increase the chemical diversity in this series, the introduction of three-point chemical diversity on the cyclopenta[b]thiophen-4-one scaffold was explored. About thirty newly functionalized thiophene-containing bicycles were obtained using various chemical reactions, paving the way for novel possibilities in medicinal chemistry projects.
Keywords: aminothiaindanone; functionalization; thiophene; multi-step synthesis